LINEAR CONGRUENT METHOD Penerapan Algoritma Linear Congruent Method Pada Pengacakan Soal Kenaikan Tingkat Karyawan Di LKP Sempoa SIP Binjai - Adhitya, Sri Ayu; Ginting, Budi Serasi; Sihombing, Marto (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
An exam is a test conducted to see and determine a person’s ability in terms of competence, knowledge and experience. By conducting an exam, an educational institution can determine whether a student can continue to the next class or not, while in a work environment, the institution can determine whether a person is entitled to be accepted as a worker or can get a promotion. Based on the journal Andilala, Gunawan (2018) about the implementation of the linear congruent method for randomizing questions in an android-based arithmetic calculation game. Said that "The linear congruent method is used as a means for randomizing the arithmetic calculation questions so that users who play will not find the same questions as other users". In conducting exams or tests for employees, SIP Sempoa still uses the manual method where all employees take exams with the same paper and number of questions. The implementation of the exam with the same number of questions is considered ineffective for determining employee competence. To avoid this problem, the author will utilize technology by using the Linear Congruent Method (LCM) to generate a random number of questions so that each employee has a question with a different number and process. exams are more effective. Based on the explanation above, the author takes the title "Application of the Linear Congruent Method Algorithm in Randomization of Employee Level Increase Problems at LKP Abacus SIP Binjai".